An Eye for Odin? Divine Role-Playing in the Age of Sutton Hoo. (2014) - Price, Neil; Mortimer, Paul
Abstract : This paper presents some new observations concerning the construction of the Sutton Hoo helmet, as a point of entry to a wider discussion of pre-Christian religious and ideological links across Scandinavia. It will be argued that in certain circumstances and locations, such as the firelit interior of the hall, the wearer of the helmet was seen as both war leader and war god, a literal personification of Odin. This interpretation is supported and extended with a variety of Scandinavian finds from the sixth to tenth centuries, and arguably represents an unusually physical manifestation of the ritual border-crossing between human and divine elites. In the socio-political context of early medieval kingdoms, the dramatic imagery of the helmets and related military equipment had a critical role to play in the communication of power, the origin of military prowess, and the religious allegiance of a warlord.